Common concern for the Arctic : Conference arranged by the Nordic Council of Ministers 9-10 September 2008, Ilulissat, Greenland (Copenhagen : Nordic Council of Ministers, 2008)
Developments in the Arctic are increasingly a subject for politi-cal dialogue and policy discussion in global and regional fora and within individual states. There is an obvious need for coor-dinated international action to meet the many challenges facing the Arctic region due to globalization and climate change. It is a fact that the rest of the world is affected by the consequences of melting ice in the Arctic. To address these issues, the Nordic Council of Ministers hosted an Arctic Conference in Ilulissat, Greenland on 9-10 September 2008 with the theme: Common Concern for the Arctic. The Conference was attended by repre-sentatives of the Nordic Countries, the member countries of the European Union, The EU-Commission and the EU-Parliament, USA, Russia, China and Korea. The Conference provided a forum for exchange of views on ac-tivities and policies, pursued by individual states and in particu-lar the European Union, that are of importance for or that di-rectly affect developments in the Arctic region. The Conference aimed at raising awareness of the new challenges and opportu-nities that are a result of changing environmental, economic and social conditions in the Arctic region. The Conference ad-dressed the role of circumpolar and regional cooperation in the implementation of governmental and EU policies and the need to enhance synergies in order to improve consistency and avoid overlapping activities. The conference proceedings and the Chairman's conclusions are included in this conference report. The Nordic Council of Minis-ters encourages all relevant stakeholders to take note of the messages from the conference and act accordingly.